Socialization, Social Integration and Psychosocial Wellbeing in Public Spaces [Socialización, Integración Social y Bienestar Psicosocial en Los Espacios Públicos] - Muñoz-Parra, C; Dziekonski-Ruchardt, M; Pavez-Lizarraga, A; Rodriguez-Araneda, M; Henriquez-Ojeda, K (Universidad Austral de Chile, 2020)
This paper addresses urban population growth and the prevalence of psychosocial discomfort in order to use the design of public spaces to help improve the quality of life of people, considering the role of public spaces in community life. There is a conceptual journey covering the quality of life in the city, looking at social integration and psychosocial wellbeing and putting an emphasis on a transdisciplinary conceptual approach. The result must match the uses, motivations, and intentions of those who use public spaces, helping to improve their quality of life and the way they understand it. We venture a definition of quality of life including a set of descriptors specified for the subsequent design process. © 2020, Universidad Austral de Chile.